A review of tests on slab-column connections with advanced concrete materials. (August 2021) - Isufi, Brisid; Pinho Ramos, António
Abstract: Advances in concrete technology during the last decades have resulted in the development of materials with enhanced mechanical properties, such as High Strength Concrete (HSC), Fibre Reinforced Concrete (FRC) and Ultra-High Performance Fibre Reinforced Concrete (UHPFRC). The application of these materials in flat slabs, which are a popular structural solution in Reinforced Concrete (RC) buildings worldwide, has the potential of significantly reducing raw material consumption by enabling the design of slenderer and therefore lighter structures. However, flat slabs are susceptible to punching shear failure, which is a complex phenomenon that remains challenging, even though significant efforts have been made to experimentally study it. For advanced concrete materials (HSC, FRC and UHPFRC), the challenge is further accentuated by the continuous and rapid development of these materials. With the purpose of identifying and highlighting gaps in the published literature, a review of tests with HSC, FRC and UHPFRC slab-column connections in non-seismic and seismic loading applications is presented in this paper. It is shown that future research directions in this field include, among others, testing thicker slabs, HSC slabs with higher concrete compressive strength, HSC combined with FRC and several more cases related to seismic loading conditions.